2023
DOI: 10.1007/s12144-023-04323-8
|View full text |Cite
|
Sign up to set email alerts
|

Digital game addiction of preschool children in the Covid-19 pandemic: social emotional development and parental guidance

Abstract: The Covid 19 pandemic has caused children to spend more time at home and an increase in their digital addiction tendencies. Children’s digital game addictions were affected by parents’ strategies and negatively affected their social and emotional development. The study was carried out in order to determine the digital game addiction tendency levels of children and the strategies applied by the parents, and to examine the correlation between the results obtained and the social-emotional development of the child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This result is not in line with the findings of current study. As a matter of fact, in the study conducted by Şenol, Şenol and Yaşar (2024), the level of digital game addiction tendency is related to parents' digital game manipulation strategies. He stated that active parental guidance strategy prevents children's tendency towards digital game addiction, while digital-focused guidance and free parental strategies increase the tendency towards addiction.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…This result is not in line with the findings of current study. As a matter of fact, in the study conducted by Şenol, Şenol and Yaşar (2024), the level of digital game addiction tendency is related to parents' digital game manipulation strategies. He stated that active parental guidance strategy prevents children's tendency towards digital game addiction, while digital-focused guidance and free parental strategies increase the tendency towards addiction.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…In their research, Gözüm and Kandır (2020b) revealed that as the duration of digital game play of preschool children increased, their tendency to play and their concentration level decreased. Şenol, Şenol and Can-Yaşar (2023) found that digital game addiction tendencies increased and their social-emotional development was negatively affected due to the fact that children could not find the opportunity to open up to the environment during the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In this survey, more than 80% of parents of young children were anxious about their children's education (Fan et al, 2024). Children in early childhood develop rapidly in cognitive, emotional and social skills (Bhavnani et al, 2021;Brodin & Renblad, 2020;Nguyen et al, 2020;Şenol et al, 2023). As children approach the age of entering elementary school, parents have increasingly high expectations of their children in terms of their learning, life, physical and mental preparations.…”
Section: Differences In Parental Educational Anxiety and Expectation ...mentioning
confidence: 99%